PENGARUH GOOD CORPORATE GOVERNANCE PADA BIAYA KEAGENAN - Sudarma, Mudyasani; Putra, I Wayan (E-Jurnal Akuntansi, 2014)
The interest of shareholders as a principal and management as an agent are not always play with the same harmony. The difference among them emerge an agency conflict which end as an agency cost. This problem causes the shareholder to push the management to applying good corporate governance.  This study aim  to explain the impact of good corporate governance on agency cost. Samples on this study selected with purposive sampling method. According to data availability, the samples consist of 45 observations. Data analyzed by using a simple linear regression technique. This research shows a good corporate governance have a significant negative impact on agency cost. Based on the result, good corporate governance implementation is proved to reduce the agency cost.
Keywords: conflict of interest, good corporate governance, agency cost.